Evaluation of anti-microbial potential of hydroxycoumarins - Fernandes, Cátia; Martins, Sérgio; Rosado, Tânia; Caldeira, Ana; Pereira, António (Universidade de Évora, 2013)
Coumarins comprise a very large class of substances found in plants and are made of fused benzene and α-pyrone rings. More than 1300 coumarins have been identified, principally as secondary metabolites in green plants but also in fungi and bacteria. Coumarin and its derivatives are considered nowadays an important class of organic compounds due to their wide spectrum of biological activities and therapeutic applications, including anticoagulant, estrogenic, dermal photosensitising, vasodilator, molluscucidal, antihelmintic, sedative and hypnotic, analgesic and hypothermic activity. A number of studies have reported anti-microbial activities of various coumarins. In contrast, there are few reports of anti-microbial potential of hydroxycoumarins. In this contest, six hydroxycoumarins were tested. The anti-microbial properties were evaluated by two different methods using Fusarium oxysporum (CCMI866), Aspergillus niger (CCMI296), Cladosporium 7F1 and Trichoderma (CCMI783) to access the antimicrobial spectrum of active compounds.
Keywords: hydroxycoumarins; anti-microbial potential